Desirability of technology entrepreneurship among Bulgarian STEM students: the role of entrepreneurship education - Yordanova, D.; Filipe, J. (European Research Studies Journal, 2018)
The aim of this study is to examine the role of entrepreneurship education for the development of desirability of technology entrepreneurship among STEM students (STEM refers to any subject that falls under the disciplines of science, technology, engineering or mathematics) in 15 Bulgarian universities. A survey was administrated to students in STEM majors in 15 Bulgarian universities in 2015 and 2016. The sample for this study is composed of 879 STEM students, who are not nascent entrepreneurs or nascent intrapreneurs (in a process of starting a business) or established business owners or intrapreneurs (have already started a business). The results reveal that STEM students included in the sample are an important source of potential entrepreneurs. This study demonstrates that entrepreneurship education is positively associated with desirability of technology entrepreneurship among Bulgarian STEM students after controlling for age, gender, entrepreneurial role models, social network support, previous experience in a technology company, perceptions of environment. Other factors with positive effect on the desirability of technology entrepreneurship include role models and support from family and friends. The empirical results have important practical implications for higher education institutions and policy makers. Greater emphasis should be placed on entrepreneurship education for STEM students in Bulgarian universities. We recommend an entrepreneurial perspective to be introduced in other courses as well. Business faculties should provide doctoral programs in entrepreneurship to train a future generation entrepreneurship academics who will be capable of using up-to-date methods in entrepreneurship education. The present study attempts to fill several research gaps identified in the literature on technology entrepreneurship and entrepreneurship education. The study responds also to the calls for more research exploring the role of entrepreneurship education particularly in the field of technology entrepreneurship.